Application of Exponential Comparison Method in Designing Decision Support Systems For Performance and Promotions Assessment in Banking Industry - Launtu, Ansir; Rahayu, Betty; Dharmawan, Donny; Fahrizal; Mertua Agung Durya, Ngurah Pandji (Jurnal Informasi dan Teknologi, 2023)
This research aims to find out how to design a decision support system for evaluating employee performance as a promotion. Data collection in this research used observation, interviews, and a literature study. The population in this study were employees. Rapid Application Development (RAD) is the system development method that the author used to create this application. The tools that the author uses in system design are UML (Unified Model Language) diagrams to show the process and data flow to be designed; Adobe Dreamweaver CS6 is used to design applications; Wamp Server is used as a webserver; and Diaportable is used to illustrate UML diagrams. Based on the results of the discussion, the following were obtained: The decision support system with MPE analysis (Exponential Comparison Method) aims to find employees who are worthy of promotion. The assessment system consists of seven, including education, work performance, discipline, communicativeness, cooperation, reasoning, encouragement of achievement, and responsibility for self-assessment, which are carried out by HRD staff and supervisors, while the HRD manager is only responsible for the decision-making process. The results of this research are in the form of graphs and accumulated MPE assessments, which show the ranking order of each candidate employee.